APLIKASI PENGETAHUAN BANGUN RUANG BERBASIS ANDROID UNTUK KELAS V SD ISLAM AT-TAQWA - Wijaya, Muhamad (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
This android-based spatial knowledge application was created as a media to support the learning of Class V students of SD Islam At-Taqwa about building space that can be done anywhere and anytime, helping students to recognize the theory and concepts of building space, in addition so that students - students have alternative learning media besides books and foster student interest in learning mathematics. Based on the application that has been made by the author, it can be concluded that, Smartphones with the Android operating system are the ones that are widely used in the community, Android is an operating system that supports script writing using the Java language, The spatial application created by the author helps in learning geometry for students. Grade V elementary school students and the general public who want to use the application to help calculate the results of calculating the area and volume of each shape and the manual calculation formula.